2021
DOI: 10.1073/pnas.2111815118
|View full text |Cite
|
Sign up to set email alerts
|

Mass spectrometric identification of immunogenic SARS-CoV-2 epitopes and cognate TCRs

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infections elicit both humoral and cellular immune responses. For the prevention and treatment of COVID-19, the disease caused by SARS-CoV-2, it has become increasingly apparent that T cell responses are equally if not more important than humoral responses in mediating recovery and immune protection. One major challenge in developing T cell–based therapies for infectious and malignant diseases has been the identification of immunogenic epitopes that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…TGSNVFQTR from spike glycoprotein (638-646) was predicted binding to A*68:01 allele and it locates within the SD1 domain. ITFGGPSDSTGSNQNGER from nucelocapsid protein (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32) was also identified in this study and has been predicted to bind to the same allele. Additionally, two class II peptides from nucleocapisd protein SPDDQIGYYRRATRRIR and FSKQLQQSMSSADSTQA were identified, which has not been reported before.…”
Section: Immunopeptidomics Identified Viral Epitopes Presented On Bot...mentioning
confidence: 56%
See 1 more Smart Citation
“…TGSNVFQTR from spike glycoprotein (638-646) was predicted binding to A*68:01 allele and it locates within the SD1 domain. ITFGGPSDSTGSNQNGER from nucelocapsid protein (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32) was also identified in this study and has been predicted to bind to the same allele. Additionally, two class II peptides from nucleocapisd protein SPDDQIGYYRRATRRIR and FSKQLQQSMSSADSTQA were identified, which has not been reported before.…”
Section: Immunopeptidomics Identified Viral Epitopes Presented On Bot...mentioning
confidence: 56%
“…The approach has been used in other viral infections, revealing new antigens including those peptide sequences that activated T-cell responses against West Nile virus 14 , HIV 15,16 and measles 17 . It was reported that epitopes of SARS-CoV-2 derived not only from structural but also non-structural genes in regions highly conserved among SARS-CoV-2 strains including recently recognized variants 18 . This included epitopes from membrane glycoprotein (MGP) and non-structure protein-13 (NSP13).…”
Section: Introductionmentioning
confidence: 99%
“…The identification of the most immunogenic epitopes is key to the study and understanding of cellular immune response to gain insights into virus-induced infection mechanisms. An immunogenic peptide is one that is presented by a self-major histocompatibility complex (MHC) and is able to elicit a T cell response [ 43 ]. Thus, the identification of such epitopes is also of importance in the context of future therapies.…”
Section: Discussionmentioning
confidence: 99%
“…In 2021, Pan et al reported identification of 4 epitopes on the SARS Co-V2 non-structural protein helicase (NSP13) and one on the membrane glycoprotein (MGP) that could be eluted from naturally processed major histocompatability complex and then demonstrated to induce the production of cytotoxic T-cells specific for the same epitopes [30]. The authors report that these 5 epitopes are coded by a highly conserved region of the SARS Co-V2 genome unchanged between the original pandemic strain and all variants available for study through mid-June 2021.…”
Section: Additional Considerations Tor Vdbp Vaccines For Sars Co-v2mentioning
confidence: 99%